Are work experience participants protected against sex discrimination or sexual harassment?. (June 2021) - Hewitt, Anne; Owens, Rosemary; Stewart, Andrew; Howe, Joanna
More and more young Australians are undertaking periods of work experience as a part of their study or independently to facilitate their transition into employment. They are often subject to a significant power disparity compared to others in the workplace, and need the placement to finish a course, and/or to get practical experience, connections and industry references. This makes them vulnerable, including to sexual harassment and sex discrimination. However, whether prohibitions of such conduct apply to them is a complex question, which this article explores.